2017
DOI: 10.1186/s40557-017-0157-0
|View full text |Cite|
|
Sign up to set email alerts
|

The current condition of the workers’ general health examination in South Korea: a retrospective study

Abstract: BackgroundBusiness owners in the Republic of Korea must take part in the workers’ general health examination. However, there have been few formal analyses of the uptake of this examination by employees. In the present study, we examined the rates of participation in medical examinations according to age group, health insurance type, and enterprise size, and then compared these results with those of the national general health screening. Furthermore, we determined the distribution of patients with abnormal resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…These values may surpass that of the general population and office workers (e.g., general affairs, administration, teachers) in Korea, considering that non-office workers (e.g., radiation workers, health care providers, drivers) receive annual health examination opportunities in the national health examination system, whereas regional policyholders and office workers receive them on a biennial basis [21,22]. In addition, examination participation (i.e., health checkups) rates of non-office workers were higher than those of regional policyholders and office workers [23]. Compared with occupational exposure, the recent annual levels of which steadily decreased around dose limits for the public (i.e., 1 mSv), levels of medical exposure are not negligible, implying that it is necessary to consider medical exposure in estimating radiation-induced health risks.…”
Section: Discussionmentioning
confidence: 99%
“…These values may surpass that of the general population and office workers (e.g., general affairs, administration, teachers) in Korea, considering that non-office workers (e.g., radiation workers, health care providers, drivers) receive annual health examination opportunities in the national health examination system, whereas regional policyholders and office workers receive them on a biennial basis [21,22]. In addition, examination participation (i.e., health checkups) rates of non-office workers were higher than those of regional policyholders and office workers [23]. Compared with occupational exposure, the recent annual levels of which steadily decreased around dose limits for the public (i.e., 1 mSv), levels of medical exposure are not negligible, implying that it is necessary to consider medical exposure in estimating radiation-induced health risks.…”
Section: Discussionmentioning
confidence: 99%
“…However, these exposures have decreased in Korea due to the shift of the economy from agriculture to the manufacturing and service sector. The increasing trend in the annual cumulative incidence of sarcoidosis might be explained by the increased detection rate of sarcoidosis due to the increased diagnostic techniques and frequent regular health check-ups [3032]. The overall participation rate in primary health examinations, including the chest X-rays, has increased from 56% in 2006 to 72% in 2013 [32].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing trend in the annual cumulative incidence of sarcoidosis might be explained by the increased detection rate of sarcoidosis due to the increased diagnostic techniques and frequent regular health check-ups [3032]. The overall participation rate in primary health examinations, including the chest X-rays, has increased from 56% in 2006 to 72% in 2013 [32]. The number of patients using computed tomography and magnetic resonance imaging, which are diagnostic tools for sarcoidosis, have also increased steadily from 4,118,434 and 631,305 in 2012 to 5,139,149 and 805,831 in 2015, respectively [33].…”
Section: Discussionmentioning
confidence: 99%
“…After publication of the original article [1] the authors found that the following affiliations were incorrect at the time of publication:Jun-Pyo MyongThe current affiliation,’ Occupational Safety and Health Research Institute, Korea Occupational Safety and Health Agency’ is incorrect.The corrected affiliation should be: Department of Occupational and Environmental Medicine, Seoul St. Mary’s Hospital, College of Medicine, Catholic University of Korea, Seoul, Republic of Korea Jong Heon ParkThe current affiliation,’ Occupational Safety and Health Research Institute, Korea Occupational Safety and Health Agency’ is incorrect.The corrected affiliation should be: Big Data Steering Department, National Health Insurance Service, Wonju, Republic of Korea …”
Section: Erratummentioning
confidence: 99%